Quality Control Analysis Using Statistical Quality Control (SQC) and Fault Tree Analysis (FTA) Methods in Semoga Laris Tofu Factory - Aini, Mutiara Qurrota; Tosungku, La Ode Ahmad Safar; Gunawan, Suwardi (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
Semoga Laris tofu factory is a business engaged in the production of tofu. This factory produces approximately 80 drums of tofu per day. There are problems faced at this factory, namely the increase in defective products, namely the texture of the tofu that is too soft, dirty tofu, and the shape of the tofu that is too thin. This can lead to decreased consumer confidence. Every day there are at least 10-15% defective products. This study was conducted to determine the types of product defects, the causes of product defects, and propose improvements to minimize defective products in tofu processing. The methods used in this research are Statistical Quality Control (SQC) and Fault Tree Analysis (FTA). The quality tools of SQC method are check sheet, histogram, pareto diagram, P control map, and fishbone diagram. Then proceed using the Fault Tree Analysis (FTA) method to determine suggestions and corrective actions. Based on the results of research using the SQC method, it is known that the number of thin size defects is 46.231, there is dirt on the tofu as many as 16.093 seeds, and the texture of soft tofu is 27.357 seeds. The results of the analysis using the fault tree analysis (FTA) method show that the causes of product defects include insufficient rest time (D2), irregular machine maintenance (E2), insufficient rest time (F1), and no temperature checker. Proposed improvements that can be given are by providing measuring instruments, making machine maintenance schedules, making machine control cards, giving breaks, supervising, giving gifts to workers, and providing thermometers.